Performance analysis of cooperative NOMA with a shared AF relay. Issue 19 (19th October 2018) - Li, Yan; Li, Yongzhao; Chen, Yunfei; Ye, Yinghui; Zhang, Hailin
Abstract : Non‐orthogonal multiple access (NOMA) has been proposed as a promising technique for the fifth generation wireless networks. In this study, the authors investigate the performance of a cooperative relaying scheme using NOMA (termed NOMA‐AF‐CRS), where two sources communicate with their corresponding destinations over the same frequency simultaneously through a shared amplify‐and‐forward (AF) relay. First, the closed‐form approximations are derived for the outage probability. The analytical results are further evaluated in the high signal‐to‐noise ratio region to characterise the diversity order achieved by the system. Then, the ergodic sum capacity of NOMA‐AF‐CRS is analysed and an upper bound to the ergodic sum capacity is derived. Finally, simulation results are presented to verify the proposed analysis and demonstrate the advantages of NOMA‐AF‐CRS over the conventional orthogonal multiple access techniques.